2018
DOI: 10.1063/1.5045370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of collision and ion Mach number on magnetized plasma sheath with two species of positive ions

Abstract: We study the effect of collision and ion Mach number in a magnetized plasma sheath having two species of positive ions using fluid model. It is assumed that both the ions are singly ionized and in thermal equilibrium, and the electrons obey Boltzmann distribution. Our work signifies that the collision greatly affects the ion densities, which explicitly affect space charge density, net current density and the transverse drift of ions. On increasing the collisional frequency, ions accumulation point and current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Foroutan [28] presented the one-dimensional fluid simulation to investigate the dynamics of an electrostatic sheath for two ion species plasma with dust grains. In recent years, the authors also worked on two ion species plasma in the presence of a uniform oblique magnetic field and collision term using kinetic and fluid models [29][30][31]. Singha et al [32,33] carried out an experiment to study the effect of a non-uniform oblique magnetic field and biasing voltage on presheath and sheath structures.…”
Section: Introductionmentioning
confidence: 99%
“…Foroutan [28] presented the one-dimensional fluid simulation to investigate the dynamics of an electrostatic sheath for two ion species plasma with dust grains. In recent years, the authors also worked on two ion species plasma in the presence of a uniform oblique magnetic field and collision term using kinetic and fluid models [29][30][31]. Singha et al [32,33] carried out an experiment to study the effect of a non-uniform oblique magnetic field and biasing voltage on presheath and sheath structures.…”
Section: Introductionmentioning
confidence: 99%
“…Once the plasma-wall interaction is well understood it will be possible to control heat loading, energy transfer and particle flow towards the wall and overall bulk plasma behavior [4,5]. The plasma sheath is one of the oldest problems in plasma [3,6] and in recent years, the sheath formed between magnetized plasma and a particle absorbing wall has received a considerable amount of attention [7][8][9][10][11]. Irrespective of this, plasma sheath is significantly influencing the charged particles and the energy flux to the wall, which in turn considerably modifies the absorption, emission impurities and all other characteristics in the plasma [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…The plasma sheath is one of the oldest problems in plasma [3,6] and in recent years, the sheath formed between magnetized plasma and a particle absorbing wall has received a considerable amount of attention [7][8][9][10][11]. Irrespective of this, plasma sheath is significantly influencing the charged particles and the energy flux to the wall, which in turn considerably modifies the absorption, emission impurities and all other characteristics in the plasma [1,11]. In typical boundary layer problems the sheath region is of several electron-Debye lengths, which is much smaller than the characteristic extension of the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the ion-neutral collision plays an important role in the formation and stability of sheath structure. The collisional plasma sheath in the presence of a magnetic field has been investigated by many researchers [3,4]. It has been observed that the collisional force affects the distribution of ion density and drift velocity [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The collisional plasma sheath in the presence of a magnetic field has been investigated by many researchers [3,4]. It has been observed that the collisional force affects the distribution of ion density and drift velocity [4][5][6]. The study of collisional plasma sheath has shown that collision alters the condition for the formation of the sheath.…”
Section: Introductionmentioning
confidence: 99%